Six exotic terrestrial earthworms (Oligochaeta: Megadrilacea: Moniligastridae, Lumbricidae, Ocnerodrilidae & Megascolecidae) newly added to Korean species biodiversity list - Blakemore, Robert J.; Cho, Joo-Lae; Park, Tae Seo (Zootaxa, 2012)
Preliminary inspection by the principal author of the NIBR Oligochaete collection, maintained by marine Annelida curator T.-S. Park, revealed several new endemic species, such as an Amynthas sp. nov. described in the current Zootaxa issue, plus three of the six exotics titled above. Three additional new exotic records are the results of recent in-country collection by the authors in early 2012 that together raise the Korean earthworm biodiversity count to ~113 named species.